Evaluation of the solid waste management in fish farming agroindustries of Coremas City – PB (Research, Society and Development, 2020)
Among the various economic activities that impact the environment, the fish agroindustry sector stands out. This activity that generates a large amount of waste in the stages of the production process, from the capture to the commercialization of the fish. In view of the above, this study aimed to learn about solid waste management in some fish agribusinesses located in the municipality of Coremas - PB, as well as to propose environmental control measures to subsidize future management plans for this type of establishment. To carry out the study, agro-industries were selected, for which field visits were made and a questionnaire was applied, in order to learn about the management of solid waste, identify the environmental impacts associated with it and the environmental perception of its owners and employees. Additionally, measures were proposed for the environmentally sound management of agro-industrial waste. Based on the results, it was observed that the vast majority of agro-industries had an environmentally inadequate management of solid waste, which has caused several negative environmental impacts associated, mainly, with the quantity and form of destination of the fish residues. It was also verified that it is necessary to elaborate and execute solid waste management plans, according to the applicable legislation (Law no. 12,305 / 2010), to regularize agro-industries and contribute to the environmental balance of the region. Finally, it is expected that the measures proposed in this study document serve as a basis for structuring solid waste management plans for small fish farming agro-industries located in Coremas - PB.